The association between maternal and paternal substance use and child substance use, internalizing and externalizing problems: a systematic review and meta‐analysis. (27th January 2023) - McGovern, Ruth; Bogowicz, Paul; Meader, Nick; Kaner, Eileen; Alderson, Hayley; Craig, Dawn; Geijer‐Simpson, Emma; Jackson, Katherine; Muir, Cassey; Salonen, Domna; Smart, Deborah; Newham, James J.
Abstract: Aims: There is substantial evidence showing an association between parental substance use and child substance use and/or mental health problems. Most research focuses upon maternal substance use, with the influence of paternal substance use often being overlooked. We aimed to investigate the differential effects of maternal and paternal substance use upon children aged 0–18 years. Methods: We used systematic review methods to identify observational studies examining the association between either maternal or paternal substance use and child substance use and/or mental health problems. The odds ratio (OR) effect measure was used, for ease of computation. We used a random‐effects model with the inverse variance method to meta‐analyse the findings from eligible studies. Results: We included 17 unique studies with a total of 47 374 child participants. Maternal and paternal substance use were both associated with increased odds of child any drug use [OR = 2.09; 95% confidence interval (CI) = 1.53, 2.86; n = 12 349 participants; three studies and OR = 2.86; 95% CI = 1.25, 6.54; n = 5692 participants; three studies, respectively], child alcohol problem use (OR = 2.16; 95% CI = 1.73, 2.71; n = 7339 participants; four studies and OR = 1.70; 95% CI = 1.36, 2.12; n = 14 219 participants; six studies), child externalizing problems (OR = 1.81; 95% CI = 1.01, 3.22; n = 1748 participants; three studies and OR = 1.60; 95% CI = 1.18, 2.17; n = 2508 participants; six studies) and child internalizing problems (OR = 1.60; 95% CI = 1.25, 2.06; n = 1748 participants; three studies and OR = 1.42; 95% CI = 1.12, 1.81; n = 2248 participants; five studies). Child any alcohol use was associated with maternal substance use only (OR = 2.26; 95% CI = 1.08, 4.70; n = 28 691 participants; five studies). Conclusions: Both maternal and paternal substance use are associated with child substance use and mental health problems.